2011
DOI: 10.1016/j.jss.2011.03.021
|View full text |Cite
|
Sign up to set email alerts
|

Requirements for Prolongation of Allograft Survival with Regulatory T Cell Infusion in Lymphosufficient Hosts

Abstract: Background For the clinical applicability of regulatory T cells (Tregs) in transplantation, it is critical to determine if donor antigen specificity is required for their immunosuppressive function. We developed an allospecific CD4+ T cell receptor transgenic (TCR-tg) mouse as a source for large numbers of Tregs with defined allospecificity and tested whether they are more effective than polyclonal Tregs at suppressing allograft rejection. Materials and Methods CD4+CD25+CD62Lhi T cells were sorted from the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
34
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 47 publications
2
34
0
1
Order By: Relevance
“…28,29 Studies in a humanized mouse model of skin transplantation as well as studies in a heart transplantation model in mice demonstrated that donor-antigen-specific Tregs more effectively suppress the alloresponse than polyclonal Treg. 43,44 Also in humans, the generation of donor-specific Treg after kidney transplantation has been reported. 45 All these studies demonstrate that donor antigen specificity is crucial for suppression of the antidonor-directed immune response, but the origin and relative contribution of different Treg subsets are unclear.…”
Section: Discussionmentioning
confidence: 99%
“…28,29 Studies in a humanized mouse model of skin transplantation as well as studies in a heart transplantation model in mice demonstrated that donor-antigen-specific Tregs more effectively suppress the alloresponse than polyclonal Treg. 43,44 Also in humans, the generation of donor-specific Treg after kidney transplantation has been reported. 45 All these studies demonstrate that donor antigen specificity is crucial for suppression of the antidonor-directed immune response, but the origin and relative contribution of different Treg subsets are unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The transfer of ex vivo-expanded Tregs in solid organ transplantation and autoimmunity faces practical limitations, including a requirement for large numbers of cells, possibly infused repeatedly, to try to effect a significant increase in Tregs (6,(43)(44)(45)(46). In comparison, a reagent-based therapeutic approach for in vivo expansion of Tregs would be more practical.…”
Section: Discussionmentioning
confidence: 99%
“…Alloantigen-specific Tregs with a much greater specificity can be generated by expansion in the presence of allogeneic PBMCs (18,19) or B cells (10,20). The potential benefit of these alloantigen-specific Tregs is targeted suppression rather than general immunosuppression and increased suppressive potency (9,(21)(22)(23)(24)(25)(26). This may translate in fewer Tregs needed to have a therapeutic effect in the patient.…”
mentioning
confidence: 99%